Forecasting of oil-spill trajectories by using SCHISM and X-band radar. (December 2018) - Chiu, Chi-Min; Huang, Ching-Jer; Wu, Li-Chung; Zhang, Yinglong Joseph; Chuang, Laurence Zsu-Hsin; Fan, Yangming; Yu, Hao-Cheng
Abstract: In this study, we propose a two-step strategy for tracking oil-spill trajectories. First, an X-band radar is established to monitor oil spills. Accordingly, we propose a radar image-processing technique for identifying the oil slicks from the nautical radar images. Second, we apply the SCHISM to determine the water surface elevations and currents at the event site and obtain the trajectories of the oil slicks using a Lagrangian particle-tracking method incorporated in the SCHISM. An oil-spill event caused by the container ship T. S. Taipei is used as a case study for testing the capability of the proposed oil-tracking strategy. The SCHISM simulation results for the fouled coastline obtained using the wind data from a nearby data buoy agree quite well with those obtained from field observations. However, the predicted fouled coastline based on the forecasted wind data is unsatisfactory. The reasons for the unsatisfactory prediction are discussed and revealed. Highlights: A two-step oil-spill forecasting system is proposed for predicting the trajectories of oil slicks. An X-band radar is set up to monitor oil spills. A procedure for detecting the oil-slick area from radar images is developed. SCHISM is applied to determine the water levels and currents, and then the trajectories of oil slicks. An oil-spill event was used to test the capability of the proposed strategy. The simulated fouled coastline agrees well with that obtained from the field observation.